Electrolyte for improving high-temperature performance and lithium ion battery
By adding additives containing benzene ring and silicon oxygen bonds to the electrolyte of lithium ion batteries, the problems of structural distortion and manganese ion dissolution at high temperatures are solved, and the high-temperature cycling performance and capacity retention rate of the battery are improved.
Patent Information
- Application Number
- CN202411736674.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-11
AI Technical Summary
Lithium manganate material is prone to Jahn-Teller effect at high temperatures, resulting in structural distortion, manganese ion dissolution and battery capacity decrease. The existing CEI films are easy to decompose at high temperatures and cannot effectively prevent manganese dissolution.
Add additives containing benzene ring and silicon oxygen bonds to the electrolyte to prevent manganese from dissolution through mechanisms such as water removal and acid removal, film formation and isolation, and improve the stability of the electrolyte.
Effectively prevent manganese ions from dissolution, improve the high-temperature cycling performance and capacity retention rate of lithium-ion batteries, and avoid the negative impact of high temperature on the battery.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery production, and in particular to an electrolyte and a lithium ion battery with improved high temperature performance. Background Art
[0002] Lithium manganese oxide (LiMn2O4) has the advantages of low price, environmental friendliness and high voltage platform, and has been considered as a promising positive electrode material for lithium-ion batteries. However, lithium manganese oxide is prone to Jahn-Teller effect under high temperature and high pressure, which causes structural distortion, resulting in manganese ion dissolution, electrolyte content reduction, battery capacity reduction, and poor cycle performance. At the same time, hydrofluoric acid (HF) produced by the reaction of LiPF6 and H2O in the electrolyte will accelerate the dissolution of manganese, causing serious capacity decay of the battery during the cycle.
[0003] The prior art adds film-forming additives to the electrolyte to form a CEI film on the positive electrode surface to protect the electrode surface. However, most CEI films are easily decomposed at high temperatures and cannot effectively prevent manganese from dissolving, and the high-temperature cycle performance of the battery is still poor. Therefore, the prior art still has shortcomings, and the battery cycle performance needs to be further improved.
[0004] The market is in urgent need of a technical solution to solve the above problems. Summary of the invention
[0005] In order to solve the above problems, the present invention discloses an electrolyte and a lithium ion battery with improved high temperature performance. The technical solution of the present invention is implemented as follows:
[0006] The first aspect of the present invention provides an electrolyte with improved high temperature performance, the electrolyte comprising a lithium salt, a film-forming aid and an organic solvent, and also comprising an additive;
[0007] The additive comprises the following structural formula:
[0008]
[0009] In the above formula, at least one of R1, R2, R3, and R4 contains a methyl group.
[0010] Preferably, the additive is selected from at least one of the compounds comprising the following structural formulas;
[0011]
[0012] Preferably, based on 100% of the mass of the electrolyte, the mass proportion of the additive is 0.1% to 3%.
[0013] Preferably, based on 100% of the mass of the electrolyte, the mass of the additive accounts for 1.5% to 2%.
[0014] Preferably, the film-forming aid includes at least one of fluoroethylene carbonate, vinylene carbonate, 1,3-propane sultone, lithium difluorooxalatoborate, lithium difluorophosphate, lithium tetrafluoroborate, and hexamethyldisilazane;
[0015] Based on the mass of the electrolyte being 100%, the mass of the film-forming aid accounts for 0.5% to 3%.
[0016] Preferably, the lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, LiBOB, LiBF4, and LiODFB;
[0017] In the electrolyte, the concentration of the lithium salt is 1.1 mol / L to 1.4 mol / L;
[0018] Preferably, the electrolyte lithium salt includes lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide;
[0019] The concentration of lithium hexafluorophosphate is 1 mol / L, and the concentration of lithium bis(fluorosulfonyl)imide is 0.3 mol / L.
[0020] Preferably, the organic solvent includes at least one of ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, propylene carbonate and diethyl carbonate.
[0021] The second aspect of the present invention provides a lithium-ion battery, which includes a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode includes a positive electrode active material, and the positive electrode active material includes lithium manganese oxide; the electrolyte is the electrolyte provided in the first aspect above.
[0022] Preferably, the negative electrode comprises a negative electrode active material, and the negative electrode active material comprises at least one of graphite, a composite material of single crystal silicon and graphite, soft carbon, and hard carbon.
[0023] The advantages of the present invention are as follows:
[0024] The present invention adds an additive containing a benzene ring and a silicon-oxygen bond to the electrolyte, which can remove water and acid from the electrolyte, preventing the electrolyte from generating HF to corrode the electrode surface; at the same time, it can also form a film on the electrode surface to isolate the electrode from contact with the electrolyte, further preventing the electrolyte from affecting the electrode.
[0025] On the other hand, the ester group in the additive makes the additive have better compatibility, which can avoid side reactions between the additive and other components in the electrolyte, improve the stability of the electrolyte, and provide a stable environment for the film formation of the positive and negative electrodes, so that the benzene ring structure and the Si-O structure form a stable interface film on the surface of the positive and negative electrodes. The interface film has good density and high quality, is not easy to decompose at high temperatures, and can protect the surface of the electrode well, thereby avoiding the impact of high temperature on the battery. DETAILED DESCRIPTION
[0026] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specific implementation methods are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the description and claims of the present invention and any variations thereof are intended to cover non-exclusive inclusions.
[0028] In the description of the specific implementation methods of the present invention, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present invention, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0029] Reference to "embodiments" in the present invention means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in the present invention may be combined with other embodiments.
[0030] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in the present invention generally indicates that the associated objects before and after are in an "or" relationship.
[0031] Throughout the present invention, numerical values represent approximate measures or limits of ranges to cover minor deviations from given values as well as embodiments with about the values mentioned and embodiments with the exact values mentioned. Except for the working examples provided at the end of the detailed description, all numerical values of parameters (e.g., amounts or conditions) in this specification (including the appended claims) should be understood to be modified by the term "about" in all cases, regardless of whether "about" actually appears before the numerical value. "About" indicates that the stated numerical value allows some minor imprecision (close to the exact value of the value to some extent; approximately or reasonably close to the value; almost). If the imprecision provided by "about" is not otherwise understood in this ordinary sense in the art, "about" as used in the present invention at least indicates the variation that can be produced by the ordinary methods of measuring and using such parameters. For example, "about" may include a variation of less than or equal to 5%, optionally less than or equal to 4%, optionally less than or equal to 3%, optionally less than or equal to 2%, optionally less than or equal to 1%, optionally less than or equal to 0.5%, and in some aspects, optionally less than or equal to 0.1%.
[0032] Additionally, disclosure of ranges includes disclosure of all values within the entire range and further divided ranges, including endpoints and sub-ranges given for such ranges.
[0033] The prior art adds a film-forming additive to the electrolyte of lithium-ion batteries containing lithium manganese oxide to form a CEI film on the positive electrode surface to protect the electrode surface. However, most CEI films are easily decomposed at high temperatures and cannot effectively prevent manganese from dissolving, and the high-temperature cycle performance of the battery is still poor. Therefore, the prior art still has shortcomings, and the battery cycle performance needs to be further improved.
[0034] In order to solve the above problem, the present invention proposes a technical solution.
[0035] The first aspect of the present invention provides an electrolyte with improved high temperature performance, the electrolyte being used for a lithium manganate lithium ion battery, the electrolyte comprising a lithium salt, an additive, a film-forming aid and an organic solvent;
[0036] The additive comprises the following structural formula:
[0037]
[0038] In the above formula, at least one of R1, R2, R3, and R4 contains a methyl group.
[0039] Through the above arrangement, the additive of the present invention contains both benzene rings and silicon-oxygen bonds, which can remove water and acid from the electrolyte, preventing the electrolyte from generating HF to corrode the electrode surface; at the same time, it can also form a film on the electrode surface to isolate the electrode from contact with the electrolyte, further preventing the electrolyte from affecting the electrode.
[0040] On the other hand, the ester group in the structural formula makes the additive have better compatibility, can avoid the additive and other components in the electrolyte to produce side reactions, improve the stability of the electrolyte, provide a stable environment for the film formation of the positive and negative electrodes, so that the benzene ring structure and the Si-O structure form a stable interface film on the surface of the positive and negative electrodes. The interface film has good density and high quality, is not easy to decompose at high temperatures, can well protect the surface of the electrode, and thus can avoid the impact of high temperature on the battery.
[0041] In some embodiments, the additive is selected from at least one of the compounds including the following structural formulas;
[0042]
[0043] The "at least one" referred to in the present invention means that any one of the above materials, or a mixture of two, three or four, can be selected. It should be noted that the above materials do not react with each other, so their physical and chemical properties will not be affected when mixed and added. It can be understood by those skilled in the art that since the above materials all include benzene rings, silicon-oxygen bonds, Si-O structures and ester groups, the same or similar technical effects can be achieved regardless of whether one of them is used or a mixture of several types is used. The present invention does not impose any restrictions on this.
[0044] In some embodiments, based on the mass of the electrolyte being 100%, the mass of the additive accounts for 0.1% to 3%.
[0045] In specific applications, the mass percentage of the additive may be 0.1%, 0.2%, 0.3%, 0.5%, 0.8%, 1%, 1.5%, 1.8%, 2.0%, 2.5%, 2.8%, 3%, etc. The above values are only examples and are not limiting.
[0046] In some preferred embodiments, based on the mass of the electrolyte being 100%, the mass of the additive accounts for 1.5% to 2%.
[0047] In specific applications, the mass percentage of the additive may be 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, etc. The above values are only examples and are not limiting.
[0048] In some embodiments, the film-forming aid includes one of fluoroethylene carbonate (FEC), vinylene carbonate (VC), 1,3-propane sultone (PS), lithium difluorooxalatoborate (LiDFOB), lithium difluorophosphate (LiPO2F2), lithium tetrafluoroborate (LiBF4), and hexamethyldisilazane (HMDS).
[0049] In some embodiments, based on the mass of the electrolyte being 100%, the mass of the film-forming aid accounts for 0.5% to 3%.
[0050] In specific applications, the mass percentage of the film-forming aid can be 0.5%, 0.8%, 1%, 1.5%, 1.8%, 2.0%, 2.5%, 2.8%, 3%, etc. The above values are only examples and are not limiting.
[0051] In some embodiments, the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), LiBOB, LiBF4, and LiODFB.
[0052] Those skilled in the art should know that in the electrolyte, the above-mentioned lithium salts do not react with each other. Therefore, without exceeding the scope of understanding of those skilled in the art, in specific applications, those skilled in the art may select any one or a combination of two or more thereof as needed, and the present invention does not impose any limitation on this.
[0053] In some embodiments, in the electrolyte, the concentration of the lithium salt is 1.1 mol / L to 1.4 mol / L.
[0054] In specific applications, the concentration of the lithium salt can be 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, etc. The above values are only examples and are not limiting.
[0055] It should be noted that when the lithium salt is selected from one of the materials listed above, the concentration of the lithium salt represents the concentration of the material in the electrolyte. When the lithium salt is selected from two or more of the materials listed above, the concentration of the lithium salt represents the sum of the concentrations of the above materials in the electrolyte.
[0056] In some specific embodiments, the electrolyte lithium salt includes lithium hexafluorophosphate (LiPF6) and lithium bis(fluorosulfonyl)imide (LiFSI);
[0057] The concentration of lithium hexafluorophosphate is 1 mol / L, and the concentration of lithium bis(fluorosulfonyl)imide is 0.3 mol / L.
[0058] In some embodiments, the organic solvent includes at least one of ethylene carbonate (EC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), propylene carbonate (PC), and diethyl carbonate (DEC).
[0059] Those skilled in the art should know that in the electrolyte, the above-mentioned organic solvents do not react with each other. Therefore, without exceeding the scope of understanding of those skilled in the art, in specific applications, those skilled in the art may select any one or a combination of two or more thereof as needed, and the present invention does not impose any limitation on this.
[0060] The second aspect of the present invention provides a lithium-ion battery, which includes a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode includes a positive electrode active material, and the positive electrode active material includes lithium manganate; the electrolyte is the electrolyte provided by the first aspect of the present invention.
[0061] In some embodiments, the positive electrode further includes a positive electrode binder, which can improve the bonding between the positive electrode active material particles and also improve the bonding between the positive electrode material layer and the positive electrode current collector.
[0062] In some embodiments, non-limiting examples of the positive electrode binder include poly(tetrafluoroethylene) (PTFE), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), nitrile rubber (NBR), styrene ethylene butylene styrene copolymer (SEBS), styrene butadiene styrene copolymer (SBS), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), sodium alginate, lithium alginate, and combinations thereof.
[0063] In some embodiments, the positive electrode further includes a positive electrode conductive agent to impart conductivity to the electrode. The conductive agent may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.
[0064] In some embodiments, the negative electrode includes a negative electrode active material. In the present invention, the specific types of the negative electrode active material are not specifically limited and can be selected according to needs. Specifically, the negative electrode active material includes at least one of graphite, a composite material of single crystal silicon and graphite, soft carbon, and hard carbon.
[0065] In some embodiments, the negative electrode active material may include a negative electrode binder. The negative electrode binder improves the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector.
[0066] In specific applications, non-limiting examples of negative electrode binders include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin, nylon, etc.
[0067] The embodiments of the present invention will be described in detail below through examples and comparative examples. All examples and comparative examples are all solid-state battery sample groups prepared by the same process, and the number of samples in each group is 20.
[0068] It should be noted that the embodiments of the present invention are not limited to these examples.
[0069] Example 1
[0070] 1. Preparation of positive electrode:
[0071] The positive electrode active material lithium manganese oxide, the conductive agent superconducting carbon (Super-P), and the binder polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 90:7:3 to form a positive electrode slurry, the positive electrode slurry is coated on both surfaces of the current collector aluminum foil, and dried at 100°C to form a positive electrode active material layer, and then cold pressed, trimmed, cut into pieces, and slit into strips to form a lithium-ion battery positive electrode.
[0072] 2. Preparation of negative electrode:
[0073] The negative electrode slurry is made of negative electrode active material graphite, conductive agent superconducting carbon (Super-P), binder sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) in a mass ratio of 96.5:1.0:1.0:1.5, coated on the current collector copper foil and dried at 90°C to form a negative electrode active material layer, and then cold pressed, trimmed, cut into pieces, and slit into strips to make the negative electrode of the lithium-ion battery.
[0074] 3. Preparation of electrolyte
[0075] Ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) are added into a container and mixed for 30 minutes to form an organic solvent. Based on the total mass of the organic solvent as 100%, the mass of ethylene carbonate (EC) accounts for 30%, the mass of dimethyl carbonate (DMC) accounts for 30%, and the mass of ethyl methyl carbonate (EMC) accounts for 40%.
[0076] Slowly add lithium salt to the organic solvent and continue stirring for 30 minutes. The lithium salt includes a certain proportion of lithium hexafluorophosphate LiPF6 and lithium bis(fluorosulfonyl)imide LiFSI.
[0077] A film-forming aid is added to the solution, and the solution is stirred for 30 minutes to make the solution uniform. The film-forming aid is a mixture of lithium difluorophosphate (LiPO2F2), vinylene carbonate (VC) and fluoroethylene carbonate (FEC).
[0078] Finally, the additives were added to the solution and stirred for 1 h to complete the preparation of the electrolyte.
[0079] In the electrolyte, the concentration of lithium hexafluorophosphate (LiPF6) is 0.9 mol / L, and the concentration of lithium bis(fluorosulfonyl)imide (LiFSI) is 0.2 mol / L.
[0080] Taking the mass of the electrolyte as 100%, the mass ratio of the additives in the electrolyte is 3.5%, and the total mass ratio of the film-forming additives is 3.5%.
[0081] The structural formula of the additive in this embodiment is as follows:
[0082]
[0083] 4. Preparation of lithium-ion batteries
[0084] The positive electrode and negative electrode prepared above are stacked in order with the separator so that the separator is between the positive and negative electrodes to obtain a bare cell. The bare cell is placed in an outer packaging shell, injected with electrolyte, and subjected to vacuum packaging, standing, forming, shaping and other processes to obtain a lithium-ion battery.
[0085] Example 2
[0086] 1. Preparation of positive electrode:
[0087] The positive electrode slurry is prepared by mixing the positive electrode active material lithium manganese oxide, the conductive agent superconducting carbon (Super-P), and the binder polyvinylidene fluoride (PVDF) evenly. The positive electrode slurry is coated on both surfaces of the current collector aluminum foil and dried at 100°C to form a positive electrode active material layer. The positive electrode slurry is then cold pressed, trimmed, cut into pieces, and slit into strips to form a lithium-ion battery positive electrode.
[0088] 2. Preparation of negative electrode:
[0089] The negative electrode slurry is made of negative electrode active material graphite, conductive agent superconducting carbon (Super-P), binder sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR), coated on the current collector copper foil and dried at 90°C to form a negative electrode active material layer, and then cold pressed, trimmed, cut into pieces, and slit into strips to make the negative electrode of the lithium-ion battery.
[0090] 3. Preparation of electrolyte
[0091] Ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) are added into a container and mixed for 30 minutes to form an organic solvent. Based on the total mass of the organic solvent as 100%, the mass of ethylene carbonate (EC) accounts for 30%, the mass of dimethyl carbonate (DMC) accounts for 30%, and the mass of ethyl methyl carbonate (EMC) accounts for 40%.
[0092] Slowly add lithium salt to the organic solvent and continue stirring for 30 minutes. The lithium salt includes a certain proportion of lithium hexafluorophosphate LiPF6 and lithium bis(fluorosulfonyl)imide LiFSI.
[0093] A film-forming aid is added to the solution, and the solution is stirred for 30 minutes to make the solution uniform. The film-forming aid is a mixture of lithium difluorophosphate (LiPO2F2), vinylene carbonate (VC) and fluoroethylene carbonate (FEC).
[0094] Finally, the additives were added to the solution and stirred for 1 h to complete the preparation of the electrolyte.
[0095] In the electrolyte, the concentration of lithium hexafluorophosphate (LiPF6) is 0.9 mol / L, and the concentration of lithium bis(fluorosulfonyl)imide (LiFSI) is 0.2 mol / L.
[0096] Taking the mass of the electrolyte as 100%, the mass ratio of the additives in the electrolyte is 3.5%, and the total mass ratio of the film-forming additives is 3.5%.
[0097] The structural formula of the additive in this embodiment is as follows:
[0098]
[0099] 4. Preparation of lithium-ion batteries
[0100] The positive electrode and negative electrode prepared above are stacked in order with the separator so that the separator is between the positive and negative electrodes to obtain a bare cell. The bare cell is placed in an outer packaging shell, injected with electrolyte, and subjected to vacuum packaging, standing, forming, shaping and other processes to obtain a lithium-ion battery.
[0101] Example 3
[0102] 1. Preparation of positive electrode:
[0103] The positive electrode active material lithium manganese oxide, the conductive agent superconducting carbon (Super-P), and the binder polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 90:7:3 to form a positive electrode slurry, the positive electrode slurry is coated on both surfaces of the current collector aluminum foil, and dried at 100°C to form a positive electrode active material layer, and then cold pressed, trimmed, cut into pieces, and slit into strips to form a lithium-ion battery positive electrode.
[0104] 2. Preparation of negative electrode:
[0105] The negative electrode slurry is made of negative electrode active material graphite, conductive agent superconducting carbon (Super-P), binder sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) in a mass ratio of 96.5:1.0:1.0:1.5, coated on the current collector copper foil and dried at 90°C to form a negative electrode active material layer, and then cold pressed, trimmed, cut into pieces, and slit into strips to make the negative electrode of the lithium-ion battery.
[0106] 3. Preparation of electrolyte
[0107] Ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) are added into a container and mixed for 30 minutes to form an organic solvent. Based on the total mass of the organic solvent as 100%, the mass of ethylene carbonate (EC) accounts for 30%, the mass of dimethyl carbonate (DMC) accounts for 30%, and the mass of ethyl methyl carbonate (EMC) accounts for 40%.
[0108] Slowly add lithium salt to the organic solvent and continue stirring for 30 minutes. The lithium salt includes a certain proportion of lithium hexafluorophosphate LiPF6 and lithium bis(fluorosulfonyl)imide LiFSI.
[0109] A film-forming aid is added to the solution, and the solution is stirred for 30 minutes to make the solution uniform. The film-forming aid is a mixture of lithium difluorophosphate (LiPO2F2), vinylene carbonate (VC) and fluoroethylene carbonate (FEC).
[0110] Finally, the additives were added to the solution and stirred for 1 h to complete the preparation of the electrolyte.
[0111] In the electrolyte, the concentration of lithium hexafluorophosphate (LiPF6) is 1 mol / L, and the concentration of lithium bis(fluorosulfonyl)imide (LiFSI) is 0.3 mol / L.
[0112] Taking the mass of the electrolyte as 100%, the mass proportion of the additive in the electrolyte is 0.1%, and the total mass proportion of the film-forming additive is 0.5%.
[0113] The structural formula of the additive in this embodiment is as follows:
[0114]
[0115] 4. Preparation of lithium-ion batteries
[0116] The positive electrode and negative electrode prepared above are stacked in order with the separator so that the separator is between the positive and negative electrodes to obtain a bare cell. The bare cell is placed in an outer packaging shell, injected with electrolyte, and subjected to vacuum packaging, standing, forming, shaping and other processes to obtain a lithium-ion battery.
[0117] Example 4
[0118] 1. Preparation of positive electrode:
[0119] The positive electrode active material lithium manganese oxide, the conductive agent superconducting carbon (Super-P), and the binder polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 90:7:3 to form a positive electrode slurry, the positive electrode slurry is coated on both surfaces of the current collector aluminum foil, and dried at 100°C to form a positive electrode active material layer, and then cold pressed, trimmed, cut into pieces, and slit into strips to form a lithium-ion battery positive electrode.
[0120] 2. Preparation of negative electrode:
[0121] The negative electrode slurry is made of negative electrode active material graphite, conductive agent superconducting carbon (Super-P), binder sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) in a mass ratio of 96.5:1.0:1.0:1.5, coated on the current collector copper foil and dried at 90°C to form a negative electrode active material layer, and then cold pressed, trimmed, cut into pieces, and slit into strips to make the negative electrode of the lithium-ion battery.
[0122] 3. Preparation of electrolyte
[0123] Ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) are added into a container and mixed for 30 minutes to form an organic solvent. Based on the total mass of the organic solvent as 100%, the mass of ethylene carbonate (EC) accounts for 30%, the mass of dimethyl carbonate (DMC) accounts for 30%, and the mass of ethyl methyl carbonate (EMC) accounts for 40%.
[0124] Slowly add lithium salt to the organic solvent and continue stirring for 30 minutes. The lithium salt includes a certain proportion of lithium hexafluorophosphate LiPF6 and lithium bis(fluorosulfonyl)imide LiFSI.
[0125] A film-forming aid is added to the solution, and the solution is stirred for 30 minutes to make the solution uniform. The film-forming aid is a mixture of lithium difluorophosphate (LiPO2F2), vinylene carbonate (VC) and fluoroethylene carbonate (FEC).
[0126] Finally, the additives were added to the solution and stirred for 1 h to complete the preparation of the electrolyte.
[0127] In the electrolyte, the concentration of lithium hexafluorophosphate (LiPF6) is 1 mol / L, and the concentration of lithium bis(fluorosulfonyl)imide (LiFSI) is 0.3 mol / L.
[0128] Taking the mass of the electrolyte as 100%, the mass proportion of the additive in the electrolyte is 0.5%, and the total mass proportion of the film-forming additive is 0.5%.
[0129] The structural formula of the additive in this embodiment is as follows:
[0130]
[0131] 4. Preparation of lithium-ion batteries
[0132] The positive electrode and negative electrode prepared above are stacked in order with the separator so that the separator is between the positive and negative electrodes to obtain a bare cell. The bare cell is placed in an outer packaging shell, injected with electrolyte, and subjected to vacuum packaging, standing, forming, shaping and other processes to obtain a lithium-ion battery.
[0133] Example 5
[0134] 1. Preparation of positive electrode:
[0135] The positive electrode active material lithium manganese oxide, the conductive agent superconducting carbon (Super-P), and the binder polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 90:7:3 to form a positive electrode slurry, the positive electrode slurry is coated on both surfaces of the current collector aluminum foil, and dried at 100°C to form a positive electrode active material layer, and then cold pressed, trimmed, cut into pieces, and slit into strips to form a lithium-ion battery positive electrode.
[0136] 2. Preparation of negative electrode:
[0137] The negative electrode slurry is made of negative electrode active material graphite, conductive agent superconducting carbon (Super-P), binder sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) in a mass ratio of 96.5:1.0:1.0:1.5, coated on the current collector copper foil and dried at 90°C to form a negative electrode active material layer, and then cold pressed, trimmed, cut into pieces, and slit into strips to make the negative electrode of the lithium-ion battery.
[0138] 3. Preparation of electrolyte
[0139] Ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) are added into a container and mixed for 30 minutes to form an organic solvent. Based on the total mass of the organic solvent as 100%, the mass of ethylene carbonate (EC) accounts for 30%, the mass of dimethyl carbonate (DMC) accounts for 30%, and the mass of ethyl methyl carbonate (EMC) accounts for 40%.
[0140] Slowly add lithium salt to the organic solvent and continue stirring for 30 minutes. The lithium salt includes a certain proportion of lithium hexafluorophosphate LiPF6 and lithium bis(fluorosulfonyl)imide LiFSI.
[0141] A film-forming aid is added to the solution, and the solution is stirred for 30 minutes to make the solution uniform. The film-forming aid is a mixture of lithium difluorophosphate (LiPO2F2), vinylene carbonate (VC) and fluoroethylene carbonate (FEC).
[0142] Finally, the additives were added to the solution and stirred for 1 h to complete the preparation of the electrolyte.
[0143] In the electrolyte, the concentration of lithium hexafluorophosphate (LiPF6) is 1 mol / L, and the concentration of lithium bis(fluorosulfonyl)imide (LiFSI) is 0.3 mol / L.
[0144] Taking the mass of the electrolyte as 100%, the mass proportion of the additive in the electrolyte is 1%, and the total mass proportion of the film-forming additive is 0.5%.
[0145] The structural formula of the additive in this embodiment is as follows:
[0146]
[0147] 4. Preparation of lithium-ion batteries
[0148] The positive electrode and negative electrode prepared above are stacked in order with the separator so that the separator is between the positive and negative electrodes to obtain a bare cell. The bare cell is placed in an outer packaging shell, injected with electrolyte, and subjected to vacuum packaging, standing, forming, shaping and other processes to obtain a lithium-ion battery.
[0149] Example 6
[0150] 1. Preparation of positive electrode:
[0151] The positive electrode active material lithium manganese oxide, the conductive agent superconducting carbon (Super-P), and the binder polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 90:7:3 to form a positive electrode slurry, the positive electrode slurry is coated on both surfaces of the current collector aluminum foil, and dried at 100°C to form a positive electrode active material layer, and then cold pressed, trimmed, cut into pieces, and slit into strips to form a lithium-ion battery positive electrode.
[0152] 2. Preparation of negative electrode:
[0153] The negative electrode slurry is made of negative electrode active material graphite, conductive agent superconducting carbon (Super-P), binder sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) in a mass ratio of 96.5:1.0:1.0:1.5, coated on the current collector copper foil and dried at 90°C to form a negative electrode active material layer, and then cold pressed, trimmed, cut into pieces, and slit into strips to make the negative electrode of the lithium-ion battery.
[0154] 3. Preparation of electrolyte
[0155] Ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) are added into a container and mixed for 30 minutes to form an organic solvent. Based on the total mass of the organic solvent as 100%, the mass of ethylene carbonate (EC) accounts for 30%, the mass of dimethyl carbonate (DMC) accounts for 30%, and the mass of ethyl methyl carbonate (EMC) accounts for 40%.
[0156] Slowly add lithium salt to the organic solvent and continue stirring for 30 minutes. The lithium salt includes a certain proportion of lithium hexafluorophosphate LiPF6 and lithium bis(fluorosulfonyl)imide LiFSI.
[0157] A film-forming aid is added to the solution, and the solution is stirred for 30 minutes to make the solution uniform. The film-forming aid is a mixture of lithium difluorophosphate (LiPO2F2), vinylene carbonate (VC) and fluoroethylene carbonate (FEC).
[0158] Finally, the additives were added to the solution and stirred for 1 h to complete the preparation of the electrolyte.
[0159] In the electrolyte, the concentration of lithium hexafluorophosphate (LiPF6) is 1 mol / L, and the concentration of lithium bis(fluorosulfonyl)imide (LiFSI) is 0.3 mol / L.
[0160] Taking the mass of the electrolyte as 100%, the mass proportion of the additive in the electrolyte is 1.5%, and the total mass proportion of the film-forming additive is 0.5%.
[0161] The structural formula of the additive in this embodiment is as follows:
[0162]
[0163] 4. Preparation of lithium-ion batteries
[0164] The positive electrode and negative electrode prepared above are stacked in order with the separator so that the separator is between the positive and negative electrodes to obtain a bare cell. The bare cell is placed in an outer packaging shell, injected with electrolyte, and subjected to vacuum packaging, standing, forming, shaping and other processes to obtain a lithium-ion battery.
[0165] Example 7
[0166] 1. Preparation of positive electrode:
[0167] The positive electrode active material lithium manganese oxide, the conductive agent superconducting carbon (Super-P), and the binder polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 90:7:3 to form a positive electrode slurry, the positive electrode slurry is coated on both surfaces of the current collector aluminum foil, and dried at 100°C to form a positive electrode active material layer, and then cold pressed, trimmed, cut into pieces, and slit into strips to form a lithium-ion battery positive electrode.
[0168] 2. Preparation of negative electrode:
[0169] The negative electrode slurry is made of negative electrode active material graphite, conductive agent superconducting carbon (Super-P), binder sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) in a mass ratio of 96.5:1.0:1.0:1.5, coated on the current collector copper foil and dried at 90°C to form a negative electrode active material layer, and then cold pressed, trimmed, cut into pieces, and slit into strips to make the negative electrode of the lithium-ion battery.
[0170] 3. Preparation of electrolyte
[0171] Ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) are added into a container and mixed for 30 minutes to form an organic solvent. Based on the total mass of the organic solvent as 100%, the mass of ethylene carbonate (EC) accounts for 30%, the mass of dimethyl carbonate (DMC) accounts for 30%, and the mass of ethyl methyl carbonate (EMC) accounts for 40%.
[0172] Slowly add lithium salt to the organic solvent and continue stirring for 30 minutes. The lithium salt includes a certain proportion of lithium hexafluorophosphate LiPF6 and lithium bis(fluorosulfonyl)imide LiFSI.
[0173] A film-forming aid is added to the solution, and the solution is stirred for 30 minutes to make the solution uniform. The film-forming aid is a mixture of lithium difluorophosphate (LiPO2F2), vinylene carbonate (VC) and fluoroethylene carbonate (FEC).
[0174] Finally, the additives were added to the solution and stirred for 1 h to complete the preparation of the electrolyte.
[0175] In the electrolyte, the concentration of lithium hexafluorophosphate (LiPF6) is 1 mol / L, and the concentration of lithium bis(fluorosulfonyl)imide (LiFSI) is 0.3 mol / L.
[0176] Taking the mass of the electrolyte as 100%, the mass proportion of the additive in the electrolyte is 2%, and the total mass proportion of the film-forming additive is 0.5%.
[0177] The structural formula of the additive in this embodiment is as follows:
[0178]
[0179] 4. Preparation of lithium-ion batteries
[0180] The positive electrode and negative electrode prepared above are stacked in order with the separator so that the separator is between the positive and negative electrodes to obtain a bare cell. The bare cell is placed in an outer packaging shell, injected with electrolyte, and subjected to vacuum packaging, standing, forming, shaping and other processes to obtain a lithium-ion battery.
[0181] Example 8
[0182] 1. Preparation of positive electrode:
[0183] The positive electrode active material lithium manganese oxide, the conductive agent superconducting carbon (Super-P), and the binder polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 90:7:3 to form a positive electrode slurry, the positive electrode slurry is coated on both surfaces of the current collector aluminum foil, and dried at 100°C to form a positive electrode active material layer, and then cold pressed, trimmed, cut into pieces, and slit into strips to form a lithium-ion battery positive electrode.
[0184] 2. Preparation of negative electrode:
[0185] The negative electrode slurry is made of negative electrode active material graphite, conductive agent superconducting carbon (Super-P), binder sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) in a mass ratio of 96.5:1.0:1.0:1.5, coated on the current collector copper foil and dried at 90°C to form a negative electrode active material layer, and then cold pressed, trimmed, cut into pieces, and slit into strips to make the negative electrode of the lithium-ion battery.
[0186] 3. Preparation of electrolyte
[0187] Ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) are added into a container and mixed for 30 minutes to form an organic solvent. Based on the total mass of the organic solvent as 100%, the mass of ethylene carbonate (EC) accounts for 30%, the mass of dimethyl carbonate (DMC) accounts for 30%, and the mass of ethyl methyl carbonate (EMC) accounts for 40%.
[0188] Slowly add lithium salt to the organic solvent and continue stirring for 30 minutes. The lithium salt includes a certain proportion of lithium hexafluorophosphate LiPF6 and lithium bis(fluorosulfonyl)imide LiFSI.
[0189] A film-forming aid is added to the solution, and the solution is stirred for 30 minutes to make the solution uniform. The film-forming aid is a mixture of lithium difluorophosphate (LiPO2F2), vinylene carbonate (VC) and fluoroethylene carbonate (FEC).
[0190] Finally, the additives were added to the solution and stirred for 1 h to complete the preparation of the electrolyte.
[0191] In the electrolyte, the concentration of lithium hexafluorophosphate (LiPF6) is 1 mol / L, and the concentration of lithium bis(fluorosulfonyl)imide (LiFSI) is 0.3 mol / L.
[0192] Taking the mass of the electrolyte as 100%, the mass proportion of the additives in the electrolyte is 3%, and the total mass proportion of the film-forming additives is 0.5%.
[0193] The structural formula of the additive in this embodiment is as follows:
[0194]
[0195] 4. Preparation of lithium-ion batteries
[0196] The positive electrode and negative electrode prepared above are stacked in order with the separator so that the separator is between the positive and negative electrodes to obtain a bare cell. The bare cell is placed in an outer packaging shell, injected with electrolyte, and subjected to vacuum packaging, standing, forming, shaping and other processes to obtain a lithium-ion battery.
[0197] Example 9
[0198] 1. Preparation of positive electrode:
[0199] The positive electrode active material lithium manganese oxide, the conductive agent superconducting carbon (Super-P), and the binder polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 90:7:3 to form a positive electrode slurry, the positive electrode slurry is coated on both surfaces of the current collector aluminum foil, and dried at 100°C to form a positive electrode active material layer, and then cold pressed, trimmed, cut into pieces, and slit into strips to form a lithium-ion battery positive electrode.
[0200] 2. Preparation of negative electrode:
[0201] The negative electrode slurry is made of negative electrode active material graphite, conductive agent superconducting carbon (Super-P), binder sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) in a mass ratio of 96.5:1.0:1.0:1.5, coated on the current collector copper foil and dried at 90°C to form a negative electrode active material layer, and then cold pressed, trimmed, cut into pieces, and slit into strips to make the negative electrode of the lithium-ion battery.
[0202] 3. Preparation of electrolyte
[0203] Ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) are added into a container and mixed for 30 minutes to form an organic solvent. Based on the total mass of the organic solvent as 100%, the mass of ethylene carbonate (EC) accounts for 30%, the mass of dimethyl carbonate (DMC) accounts for 30%, and the mass of ethyl methyl carbonate (EMC) accounts for 40%.
[0204] Slowly add lithium salt to the organic solvent and continue stirring for 30 minutes. The lithium salt includes a certain proportion of lithium hexafluorophosphate LiPF6 and lithium bis(fluorosulfonyl)imide LiFSI.
[0205] A film-forming aid is added to the solution, and the solution is stirred for 30 minutes to make the solution uniform. The film-forming aid is a mixture of lithium difluorophosphate (LiPO2F2), vinylene carbonate (VC) and fluoroethylene carbonate (FEC).
[0206] Finally, the additives were added to the solution and stirred for 1 h to complete the preparation of the electrolyte.
[0207] In the electrolyte, the concentration of lithium hexafluorophosphate (LiPF6) is 1 mol / L, and the concentration of lithium bis(fluorosulfonyl)imide (LiFSI) is 0.3 mol / L.
[0208] Taking the mass of the electrolyte as 100%, the mass ratio of the additives in the electrolyte is 2%, and the total mass ratio of the film-forming additives is 1.5%.
[0209] The structural formula of the additive in this embodiment is as follows:
[0210]
[0211] 4. Preparation of lithium-ion batteries
[0212] The positive electrode and negative electrode prepared above are stacked in order with the separator so that the separator is between the positive and negative electrodes to obtain a bare cell. The bare cell is placed in an outer packaging shell, injected with electrolyte, and subjected to vacuum packaging, standing, forming, shaping and other processes to obtain a lithium-ion battery.
[0213] Example 10
[0214] 1. Preparation of positive electrode:
[0215] The positive electrode active material lithium manganese oxide, the conductive agent superconducting carbon (Super-P), and the binder polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 90:7:3 to form a positive electrode slurry, the positive electrode slurry is coated on both surfaces of the current collector aluminum foil, and dried at 100°C to form a positive electrode active material layer, and then cold pressed, trimmed, cut into pieces, and slit into strips to form a lithium-ion battery positive electrode.
[0216] 2. Preparation of negative electrode:
[0217] The negative electrode slurry is made of negative electrode active material graphite, conductive agent superconducting carbon (Super-P), binder sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) in a mass ratio of 96.5:1.0:1.0:1.5, coated on the current collector copper foil and dried at 90°C to form a negative electrode active material layer, and then cold pressed, trimmed, cut into pieces, and slit into strips to make the negative electrode of the lithium-ion battery.
[0218] 3. Preparation of electrolyte
[0219] Ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) are added into a container and mixed for 30 minutes to form an organic solvent. Based on the total mass of the organic solvent as 100%, the mass of ethylene carbonate (EC) accounts for 30%, the mass of dimethyl carbonate (DMC) accounts for 30%, and the mass of ethyl methyl carbonate (EMC) accounts for 40%.
[0220] Slowly add lithium salt to the organic solvent and continue stirring for 30 minutes. The lithium salt includes a certain proportion of lithium hexafluorophosphate LiPF6 and lithium bis(fluorosulfonyl)imide LiFSI.
[0221] A film-forming aid is added to the solution, and the solution is stirred for 30 minutes to make the solution uniform. The film-forming aid is a mixture of lithium difluorophosphate (LiPO2F2), vinylene carbonate (VC) and fluoroethylene carbonate (FEC).
[0222] Finally, the additives were added to the solution and stirred for 1 h to complete the preparation of the electrolyte.
[0223] In the electrolyte, the concentration of lithium hexafluorophosphate (LiPF6) is 1 mol / L, and the concentration of lithium bis(fluorosulfonyl)imide (LiFSI) is 0.3 mol / L.
[0224] Taking the mass of the electrolyte as 100%, the mass proportion of the additive in the electrolyte is 2%, and the total mass proportion of the film-forming additive is 2%.
[0225] The structural formula of the additive in this embodiment is as follows:
[0226]
[0227] 4. Preparation of lithium-ion batteries
[0228] The positive electrode and negative electrode prepared above are stacked in order with the separator so that the separator is between the positive and negative electrodes to obtain a bare cell. The bare cell is placed in an outer packaging shell, injected with electrolyte, and subjected to vacuum packaging, standing, forming, shaping and other processes to obtain a lithium-ion battery.
[0229] Embodiment 11
[0230] 1. Preparation of positive electrode:
[0231] The positive electrode active material lithium manganese oxide, the conductive agent superconducting carbon (Super-P), and the binder polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 90:7:3 to form a positive electrode slurry, the positive electrode slurry is coated on both surfaces of the current collector aluminum foil, and dried at 100°C to form a positive electrode active material layer, and then cold pressed, trimmed, cut into pieces, and slit into strips to form a lithium-ion battery positive electrode.
[0232] 2. Preparation of negative electrode:
[0233] The negative electrode slurry is made of negative electrode active material graphite, conductive agent superconducting carbon (Super-P), binder sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) in a mass ratio of 96.5:1.0:1.0:1.5, coated on the current collector copper foil and dried at 90°C to form a negative electrode active material layer, and then cold pressed, trimmed, cut into pieces, and slit into strips to make the negative electrode of the lithium-ion battery.
[0234] 3. Preparation of electrolyte
[0235] Ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) are added into a container and mixed for 30 minutes to form an organic solvent. Based on the total mass of the organic solvent as 100%, the mass of ethylene carbonate (EC) accounts for 30%, the mass of dimethyl carbonate (DMC) accounts for 30%, and the mass of ethyl methyl carbonate (EMC) accounts for 40%.
[0236] Slowly add lithium salt to the organic solvent and continue stirring for 30 minutes. The lithium salt includes a certain proportion of lithium hexafluorophosphate LiPF6 and lithium bis(fluorosulfonyl)imide LiFSI.
[0237] A film-forming aid is added to the solution, and the solution is stirred for 30 minutes to make the solution uniform. The film-forming aid is a mixture of lithium difluorophosphate (LiPO2F2), vinylene carbonate (VC) and fluoroethylene carbonate (FEC).
[0238] Finally, the additives were added to the solution and stirred for 1 h to complete the preparation of the electrolyte.
[0239] In the electrolyte, the concentration of lithium hexafluorophosphate (LiPF6) is 1 mol / L, and the concentration of lithium bis(fluorosulfonyl)imide (LiFSI) is 0.2 mol / L.
[0240] Taking the mass of the electrolyte as 100%, the mass proportion of the additive in the electrolyte is 2%, and the total mass proportion of the film-forming additive is 2%.
[0241] The structural formula of the additive in this embodiment is as follows:
[0242]
[0243] 4. Preparation of lithium-ion batteries
[0244] The positive electrode and negative electrode prepared above are stacked in order with the separator so that the separator is between the positive and negative electrodes to obtain a bare cell. The bare cell is placed in an outer packaging shell, injected with electrolyte, and subjected to vacuum packaging, standing, forming, shaping and other processes to obtain a lithium-ion battery.
[0245] Example 12
[0246] 1. Preparation of positive electrode:
[0247] The positive electrode active material lithium manganese oxide, the conductive agent superconducting carbon (Super-P), and the binder polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 90:7:3 to form a positive electrode slurry, the positive electrode slurry is coated on both surfaces of the current collector aluminum foil, and dried at 100°C to form a positive electrode active material layer, and then cold pressed, trimmed, cut into pieces, and slit into strips to form a lithium-ion battery positive electrode.
[0248] 2. Preparation of negative electrode:
[0249] The negative electrode slurry is made of negative electrode active material graphite, conductive agent superconducting carbon (Super-P), binder sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) in a mass ratio of 96.5:1.0:1.0:1.5, coated on the current collector copper foil and dried at 90°C to form a negative electrode active material layer, and then cold pressed, trimmed, cut into pieces, and slit into strips to make the negative electrode of the lithium-ion battery.
[0250] 3. Preparation of electrolyte
[0251] Ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) are added into a container and mixed for 30 minutes to form an organic solvent. Based on the total mass of the organic solvent as 100%, the mass of ethylene carbonate (EC) accounts for 30%, the mass of dimethyl carbonate (DMC) accounts for 30%, and the mass of ethyl methyl carbonate (EMC) accounts for 40%.
[0252] Slowly add lithium salt to the organic solvent and continue stirring for 30 minutes. The lithium salt includes a certain proportion of lithium hexafluorophosphate LiPF6 and lithium bis(fluorosulfonyl)imide LiFSI.
[0253] A film-forming aid is added to the solution, and the solution is stirred for 30 minutes to make the solution uniform. The film-forming aid is a mixture of lithium difluorophosphate (LiPO2F2), vinylene carbonate (VC) and fluoroethylene carbonate (FEC).
[0254] Finally, the additives were added to the solution and stirred for 1 h to complete the preparation of the electrolyte.
[0255] In the electrolyte, the concentration of lithium hexafluorophosphate (LiPF6) is 1.0 mol / L, and the concentration of lithium bis(fluorosulfonyl)imide (LiFSI) is 0.4 mol / L.
[0256] Taking the mass of the electrolyte as 100%, the mass proportion of the additive in the electrolyte is 2%, and the total mass proportion of the film-forming additive is 2%.
[0257] The structural formula of the additive in this embodiment is as follows:
[0258]
[0259] 4. Preparation of lithium-ion batteries
[0260] The positive electrode and negative electrode prepared above are stacked in order with the separator so that the separator is between the positive and negative electrodes to obtain a bare cell. The bare cell is placed in an outer packaging shell, injected with electrolyte, and subjected to vacuum packaging, standing, forming, shaping and other processes to obtain a lithium-ion battery.
[0261] Embodiment 13
[0262] 1. Preparation of positive electrode:
[0263] The positive electrode active material lithium manganese oxide, the conductive agent superconducting carbon (Super-P), and the binder polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 90:7:3 to form a positive electrode slurry, the positive electrode slurry is coated on both surfaces of the current collector aluminum foil, and dried at 100°C to form a positive electrode active material layer, and then cold pressed, trimmed, cut into pieces, and slit into strips to form a lithium-ion battery positive electrode.
[0264] 2. Preparation of negative electrode:
[0265] The negative electrode slurry is made of negative electrode active material graphite, conductive agent superconducting carbon (Super-P), binder sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) in a mass ratio of 96.5:1.0:1.0:1.5, coated on the current collector copper foil and dried at 90°C to form a negative electrode active material layer, and then cold pressed, trimmed, cut into pieces, and slit into strips to make the negative electrode of the lithium-ion battery.
[0266] 3. Preparation of electrolyte
[0267] Ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) are added into a container and mixed for 30 minutes to form an organic solvent. Based on the total mass of the organic solvent as 100%, the mass of ethylene carbonate (EC) accounts for 30%, the mass of dimethyl carbonate (DMC) accounts for 30%, and the mass of ethyl methyl carbonate (EMC) accounts for 40%.
[0268] Slowly add lithium salt to the organic solvent and continue stirring for 30 minutes. The lithium salt includes a certain proportion of lithium hexafluorophosphate LiPF6 and lithium bis(fluorosulfonyl)imide LiFSI.
[0269] A film-forming aid is added to the solution, and the solution is stirred for 30 minutes to make the solution uniform. The film-forming aid is a mixture of lithium difluorophosphate (LiPO2F2), vinylene carbonate (VC) and fluoroethylene carbonate (FEC).
[0270] Finally, the additives were added to the solution and stirred for 1 h to complete the preparation of the electrolyte.
[0271] In the electrolyte, the concentration of lithium hexafluorophosphate (LiPF6) is 1 mol / L, and the concentration of lithium bis(fluorosulfonyl)imide (LiFSI) is 0.4 mol / L.
[0272] Taking the mass of the electrolyte as 100%, the mass proportion of the additive in the electrolyte is 2%, and the total mass proportion of the film-forming additive is 3%.
[0273] The structural formula of the additive in this embodiment is as follows:
[0274]
[0275] 4. Preparation of lithium-ion batteries
[0276] The positive electrode and negative electrode prepared above are stacked in order with the separator so that the separator is between the positive and negative electrodes to obtain a bare cell. The bare cell is placed in an outer packaging shell, injected with electrolyte, and subjected to vacuum packaging, standing, forming, shaping and other processes to obtain a lithium-ion battery.
[0277] Comparative Example
[0278] 1. Preparation of positive electrode:
[0279] The positive electrode active material lithium manganese oxide, the conductive agent superconducting carbon (Super-P), and the binder polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 90:7:3 to form a positive electrode slurry, the positive electrode slurry is coated on both surfaces of the current collector aluminum foil, and dried at 100°C to form a positive electrode active material layer, and then cold pressed, trimmed, cut into pieces, and slit into strips to form a lithium-ion battery positive electrode.
[0280] 2. Preparation of negative electrode:
[0281] The negative electrode slurry is made of negative electrode active material graphite, conductive agent superconducting carbon (Super-P), binder sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) in a mass ratio of 96.5:1.0:1.0:1.5, coated on the current collector copper foil and dried at 90°C to form a negative electrode active material layer, and then cold pressed, trimmed, cut into pieces, and slit into strips to make the negative electrode of the lithium-ion battery.
[0282] 3. Preparation of electrolyte
[0283] Ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) are added into a container and mixed for 30 minutes to form an organic solvent. Based on the total mass of the organic solvent as 100%, the mass of ethylene carbonate (EC) accounts for 30%, the mass of dimethyl carbonate (DMC) accounts for 30%, and the mass of ethyl methyl carbonate (EMC) accounts for 40%.
[0284] Slowly add lithium salt to the organic solvent and continue stirring for 30 minutes to form an electrolyte. The lithium salt includes a certain proportion of lithium hexafluorophosphate LiPF6 and lithium bis(fluorosulfonyl)imide LiFSI. In the electrolyte, the concentration of lithium hexafluorophosphate (LiPF6) is 0.9 mol / L, and the concentration of lithium bis(fluorosulfonyl)imide (LiFSI) is 0.2 mol / L.
[0285] 4. Preparation of lithium-ion batteries
[0286] The positive electrode and negative electrode prepared above are stacked in order with the separator so that the separator is between the positive and negative electrodes to obtain a bare cell. The bare cell is placed in an outer packaging shell, injected with electrolyte, and subjected to vacuum packaging, standing, forming, shaping and other processes to obtain a lithium-ion battery.
[0287] Comparative experiment
[0288] A total of 14 groups of samples from the above embodiments 1-13 and comparative examples were taken and the following tests were performed respectively. All test data were averaged and some values were rounded off.
[0289] 1. 400 cycles performance test at 55°C:
[0290] The battery was tested at 55°C as follows: the divided battery was charged to 4.2V with 1C constant current and constant voltage, with a cut-off rate of 0.05C; then discharged to 3V with 1C constant current. After such charge / discharge cycles, the capacity retention rate after the target number of cycles was calculated to evaluate its cycle performance. Among them, the target number of cycles at 55°C is 400 times.
[0291] 2. Capacity recovery rate at 55°C for 7 days:
[0292] The divided battery is charged to 4.2V with 1C constant current and constant voltage, with a cut-off rate of 0.05C; after being fully charged for 7 days, it is discharged to 3V, and then a complete charge and discharge process is carried out again.
[0293] The test results are shown in the following table:
[0294]
[0295]
[0296] It can be seen from the above table:
[0297] It can be seen from the embodiments and comparative examples that
[0298] Compared with Comparative Example 1, Example 1-2 adds additives and film-forming aids to the electrolyte, and its high-temperature capacity retention rate and high-temperature capacity recovery rate are improved.
[0299] In Examples 3-8, when the proportion of the film-forming aid content and the lithium salt concentration remain unchanged, as the mass proportion of the additive in the electrolyte increases, the high-temperature cycle performance and high-temperature capacity retention performance of the battery will also improve accordingly.
[0300] In Examples 7, 9 and 10, when the proportion of additive content and lithium salt concentration remain unchanged, as the mass proportion of the film-forming aid in the electrolyte increases, the high-temperature cycle performance and high-temperature capacity retention performance of the battery will first increase and then decrease.
[0301] In Examples 10 and 11, when the proportions of the film-forming aid and the additive contents remain unchanged, the lithium salt component is reduced, and the high-temperature capacity retention rate and the high-temperature capacity recovery rate are both reduced.
[0302] In Examples 12 and 13, when the additive content ratio and lithium salt concentration remain unchanged, the high-temperature cycle performance and high-temperature capacity retention performance of the battery decrease by increasing the content ratio of the film-forming aid. This shows that the higher the content of the film-forming aid, the better.
[0303] According to the above content, additives and film-forming aids can effectively improve the high-temperature cycle performance and high-temperature capacity retention performance of lithium-ion batteries containing lithium manganese oxide. In addition, the mass proportion of additives and film-forming aids in the electrolyte is positively correlated with the high-temperature cycle performance and high-temperature capacity retention performance within a certain range.
[0304] It should be pointed out that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An electrolyte with improved high temperature performance, characterized in that: The electrolyte includes a lithium salt, a film-forming aid and an organic solvent, and also includes an additive; The additive comprises the following structural formula: In the above formula, at least one of R1, R2, R3, and R4 contains a methyl group.
2. The electrolyte according to claim 1, characterized in that The additive is selected from at least one of the compounds including the following structural formulas; 3. The electrolyte according to claim 1 or 2, characterized in that Taking the mass of the electrolyte as 100%, the mass of the additive accounts for 0.1% to 3%.
4. The electrolyte according to claim 3, characterized in that Taking the mass of the electrolyte as 100%, the mass of the additive accounts for 1.5% to 2%.
5. The electrolyte according to claim 1 or 2, characterized in that: The film-forming aid includes at least one of fluoroethylene carbonate, vinylene carbonate, 1,3-propane sultone, lithium difluorooxalatoborate, lithium difluorophosphate, lithium tetrafluoroborate, and hexamethyldisilazane.
6. The electrolyte according to claim 5, characterized in that Based on the mass of the electrolyte being 100%, the mass of the film-forming aid accounts for 0.5% to 3%.
7. The electrolyte according to claim 1 or 2, characterized in that: The lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, LiBOB, LiBF4, and LiODFB.
8. The electrolyte according to claim 7, characterized in that In the electrolyte, the concentration of the lithium salt is 1.1 mol / L to 1.4 mol / L.
9. The electrolyte according to claim 1 or 2, characterized in that: The organic solvent includes at least one of ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, propylene carbonate and diethyl carbonate.
10. A lithium ion battery comprising a positive electrode, a negative electrode and an electrolyte, characterized in that: in, The positive electrode comprises a positive electrode active material, and the positive electrode active material comprises lithium manganate; the electrolyte is the electrolyte according to any one of claims 1 to 9.